Automatic Inference of Semantic Deep Structure Rules in Generative Semantic Grammars - Klein, Sheldon (University of Wisconsin-Madison Department of Computer Sciences, 1973)
Techniques and methodology for the automatic inference of semantic deep structure rules in generative semantic grammars. The key conceptual devices include a representation of semantic deep structure in the notation of a 4-dimensional network with properties of at least the 2nd-order predicate calculus, and also in the notation of a compiler-driven behavioral simulation language that describes and modifies the linguistic and extra-linguistic conceptual universe of speakers. The system is able to make grammatical-semantic inferences within the frameworks of all current generative semantic linguistic models, including the case grammar of Fillmore, the presuppositional model of Lakoff, and the 1972 semantic theory of Katz.